The role of Hepatitis B Core Antibody: Significance and Clinical practice - Phan, Thi Hang Giang; Le, Ba Hua; Phan, Ngoc Dan Thanh; Nguyen, Thi Huyen; Tran, Long Anh; Tran, Thi Bich Ngoc; Truong, Thi Bich Phuong; Nguyen, Thi Phuoc; Phan, Thi Minh Phuong (Tạp chí Y Dược Huế, 2022)
Hepatitis B infection remains a global health problem, with progression to acute-chronic hepatitis, severe liver failure, and death making hepatitis B one of the most serious infections worldwide. The disease is most widely transmitted from an infected mother to her baby, after exposure to infected blood or body fluids or unsafe sexual contact. Pregnant women, adolescents, and all adults at high risk for chronic infection are recommended to be screened for hepatitis B. Serological tests allow the distinction between acute and chronic hepatitis. Meanwhile, the molecular tests performed provide detection and quantification of viral DNA, genotyping, drug resistance, and pre-core/core mutation analysis to confirm infection and follow monitoring disease progression in patients with chronic hepatitis B. Because, the current treatment is only based on nucleotide analogs and pegylated interferons that save lives by decreasing liver cancer death, liver transplant, slowing or reversing the progression of liver disease as well as the virus infectivity. In this review, we clearly light the role of Hepatitis B Core Antibody, therefore clinicians understand the need to screen for hepatitis B core antigen (Anti-HBc), proper interpretation of HBV biomarkers, and that “anti-HBc only” indicates HBV exposure, lifelong persistence of cccDNA with incomplete infection control, and potential risk for reactivation.